Association of blood cadmium, lead, and mercury with anxiety: a cross-sectional study from NHANES 2007–2012 - Long Bai; Zongliang Wen; Zongliang Wen; Zongliang Wen; Yan Zhu; Hamdi Abdirizak Jama; Joyce D. Sawmadal; Jialin Chen (Frontiers in Public Health, 2024)
ObjectivesThe purpose of this paper is to explore the relationship between blood levels of cadmium, lead, and mercury and anxiety in American adults.MethodsBlood metals and self-reported anxiety days were extracted from laboratory data and questionnaire data, respectively, using NHANES data from 2007–2012. Weighted logistic regression was used to assess the relationship between cadmium, lead and mercury with anxiety. Restricted cubic spline was used to visualize the non-linear relationship between metal concentrations and anxiety. Weighted quantile sum (WQS) regression was used to investigate the effect of combined exposure to the three metals on anxiety.ResultsThe prevalence of anxiety in adults was 26.0%. After adjusting for potential confounding variables, cadmium levels in the highest quartile (Q4) were associated with a higher risk of anxiety compared to the lowest quartile (Q1) (OR = 1.279, 95% CI: 1.113–1.471, p < 0.01). Restricted cubic spline analysis indicated a positive association between blood cadmium levels and anxiety. Furthermore, co-exposure to multiple heavy metals was positively associated with anxiety risk (WQS positive: OR = 1.068, 95% CI: 1.016–1.160, p < 0.05), with cadmium contributing the most to the overall mixture effect. Compared to the Light RPA, the Vigorous/Moderate RPA group had a relatively low risk of anxiety after cadmium exposure.ConclusionHigh levels of blood cadmium are positively associated with the development of anxiety disorders, which needs to be further verified in future studies.